Applied elasticity and plasticity - Kassir, Mumtaz (CRC Press, Taylor & Francis Group, 2018)
Applied Elasticity and Plasticity is a comprehensive work that introduces graduate students and professionals in civil, mechanical, aeronautical and metallurgical engineering to the basic theories of elasticity, plasticity and their practical applications. Based on experimental data of static tension tests of material, several elastic and plastic stress-strain relations are derived, and commonly-used yield criteria and strain hardening rules are discussed as well.